Integration of Conflicts Resolution Values in Learning of History: a Case Studi in Kerinci - Firza Firza (Yupa: Historical Studies Journal, 2018)
Conflict is categorized as something always exist in society, people cannot be separated from conflict. Conflict causes stunted progress and development of human thought. Thus, conflicts must be immediately resolved to create a society of peace and harmony. Conflict resolution is a cultural form exists in society. Kerinci people are so familiar with conflict resolution with the term of Mandawah. In the conflict resolution of Mandawah, it is contained in traditional values that are relevant to the life of nowadays’ society. Schools do not only teach learners to master learning, but also to shape the affective aspects. Integration of conflicts resolution values in learning history is needed to improve harmonization in the life of the Kerinci society.